Meta-Analysis of Single-Case Research Design Studies on Instructional Pacing. (November 2016) - Tincani, Matt; De Mers, Marilyn
More than four decades of research on instructional pacing has yielded varying and, in some cases, conflicting findings. The purpose of this meta-analysis was to synthesize single-case research design (SCRD) studies on instructional pacing to determine the relative benefits of brisker or slower pacing. Participants were children and youth with and without disabilities in educational settings, excluding higher education. Tau-U, a non-parametric statistic for analyzing data in SCRD studies, was used to determine effect size estimates. The article extraction yielded 13 instructional pacing studies meeting contemporary standards for high quality SCRD research. Eleven of the 13 studies reported small to large magnitude effects when two or more pacing parameters were compared, suggesting that instructional pacing is a robust instructional variable. Brisker instructional pacing with brief inter-trial interval (ITI) produced small increases in correct responding and medium to large reductions in challenging behavior compared with extended ITI. Slower instructional pacing with extended wait-time produced small increases in correct responding, but also produced small increases in challenging behavior compared with brief wait-time. Neither brief ITI nor extended wait-time meets recently established thresholds for evidence-based practice, highlighting the need for further instructional pacing research.